2021
DOI: 10.20944/preprints202105.0253.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental Health, Information and Being Connected: Qualitative Experiences of social media use during the Covid-19 pandemic from a trans-national sample

Abstract: Background Due to the Covid-19 pandemic and the strict national policies regarding social distancing behavior in Europe, America and Australia, people became reliant on social media as a means for gathering information and a tool for staying connected to family, friends and work. This is the first trans-national study exploring the qualitative experiences and challenges of using social media while in lockdown or shelter in place during the current pandemic. Methods This study was part of a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…Other research reported that social media use was linked to less positive well-being (Geirdal et al, 2021;Lee et al, 2022), lower levels of happiness (Muñiz-Velázquez et al, 2021), and increased feelings Psychology of loneliness (Rumas et al, 2021;Schoultz et al, 2021). Some individuals even felt exhausted from spending too much time online to stay connected with others (Schoultz et al, 2021). Similarly, entertainment use of social networking sites was found to be associated with psychological distress symptoms (Al-Dwaikat et al, 2020).…”
Section: Research On Social Media Use During Covid-19mentioning
confidence: 98%
See 4 more Smart Citations
“…Other research reported that social media use was linked to less positive well-being (Geirdal et al, 2021;Lee et al, 2022), lower levels of happiness (Muñiz-Velázquez et al, 2021), and increased feelings Psychology of loneliness (Rumas et al, 2021;Schoultz et al, 2021). Some individuals even felt exhausted from spending too much time online to stay connected with others (Schoultz et al, 2021). Similarly, entertainment use of social networking sites was found to be associated with psychological distress symptoms (Al-Dwaikat et al, 2020).…”
Section: Research On Social Media Use During Covid-19mentioning
confidence: 98%
“…The sustained exposure to the volume of (mis)information and conversations about COVID-19 online induced anxiety (Muñiz-Velázquez et al, 2021) and overwhelmed users (Fu et al, 2020;Islam et al, 2020). Information overload was often linked with anger, frustration, and fear (Schoultz et al, 2021). Because the prevalent themes listed above coincided with the pre-pandemic social media literature, the current study still focused on perceived changes in three needs: socialization, information, and entertainment in response to the social distancing requirements of the pandemic.…”
Section: Research On Social Media Use During Covid-19mentioning
confidence: 98%
See 3 more Smart Citations